Detecting envelope wages with e-billing information - Monica Calijuri; Carola Pessino; Andrea Lopez-Luzuriaga; Simeon Schächtele; Ubaldo Gonzalez; Carla Chamorro (Inter-American Development Bank (IDB), 2023)
This paper studies tax evasion in the form of under-reported wages in Ecuador using microdata from a combination of electronic billing and personal income tax returns filed in 2017. Bringing together this novel combination of data, the study applies the standard method Pissarides and Weber (1989) used to estimate the under-reporting of income by comparing public- and private-sector employees. The results demonstrate empirically that under-reporting of income in private-sector employees is between 7 and 9 percent of their income, which translates to an estimated 3 percent of unregistered GDP. The under-reporting has important implications for social security, reducing these contributions by about 10 percent. Beyond the overall picture of under-reporting, the study detects substantial heterogeneities concerning firm size, concluding that the gap size is negatively correlated with the number of employees at the firm, which is consistent with different risks and administrative costs of envelope wages in small versus large firms.
Keywords: H24; H26; D83; 330; income tax; evasion; electronicbilling